Komponent kulturowy w nauczaniu słownictwa na zajęciach z języka obcego na poziomie akademickim na przykładzie języka włoskiego –watykańskie kulinaryzmy jako kulturemy i elementy socjolektalne - Godzich, Anna; Machowski, Szymon (Neofilolog, 2023)
Meals are commonly known to be a crucial element of life, culture and interpersonal relationships in the Italian Peninsula. In Italian dictionaries of phraseology, idiomatic expressions representing names of culinary items are the vast majority of dictionary items. This is a sign of the importance of meals, also considered as feasting together and the Italian food centrism. As the cultural component is an integral element of language education at an academic level, Italian culinary items as components of idiomatic and fixed expressions in Vatican culinary items related to culturally rooted habits and secular Catholic rituals will be analyzed. The study presented in the paper aims at: 1. clarifying the sociolect specifics of the Vatican’s clergy and kitchen staff members; 2. determining the importance of food in the socio-cultural reality in the Vatican as a type of a culture code and an element of the regional/national culture; 3. emphasizing the essence of semantic and lexical problems related to food in academic intercultural didactics, e.g. a specialization proseminar in linguistics or translation studies or a university instructor’s own thematic seminar on culinary matters in the Italian Peninsula.